Assay for detecting technical proteolytic enzymes in beer - Kupetz, Michael; Gastl, Martina; Becker, Thomas; Heinrich, Thomas (BrewingScience, 2021)
The chemical-physical stability is an important characteristic of filtered beer. Since proteins are a main cause of haze in beer, different methods in praxis application to reduce this haze formation have been developed such as an adsorption on silica gel or bentonite as well as an enzymatic breakdown. Since proteolytic enzymes can have a very selective activity on their substrate and are easy to handle, this type of stabilization is often used outside the German purity law. However, due to high inactivation temperatures and an application after boiling process, activities of these enzymes can still be present in the bottled beer. To detect potential rest activities, the aim of this publication was to develop a sensitive and reproducible method for the detection of the proteolytic enzyme activity in beer. Due to the specific activity of these enzymes on proline containing proteins, a proline rich substrate (StabiProlin?) was dosed into the beers and the residual concentration of gliadin (substrate) was determined after 24 hours of incubation. Blank samples resulted in no significant (P > 0.05) decrease in gliadin concentration, whereas the content of gliadin in beer containing proteolytic enzymes was significantly (P < 0.05) reduced over time. Despite pasteurization up to 1000 PE of the enzyme-inoculated beer, a high breakdown of gliadin (20-100 %) could be determined. This was also confirmed in 11 practice beer samples (20-75 %). Purity law brewed beers showed no decrease in gliadin concentration. Thus, application of this method can be recommended to optimize beer stabilization using proteolytic enzymes, to select suitable enzyme preparations and especially to adjust the dosage amount of stabilizing enzymes.